Tissue culture of the monocot (Mongolian Journal of Agricultural Sciences, 2014)
PsbS is a 22-kDa protein of photosystem II involved in nonphotochemical quenching of chlorophyll fluorescence but the mechanism is still unclear. We designed and generated transgenic rice plants with significantly reduced PsbS1 protein level using RNA interference (RNAi). Transformation confirmed by vector-specific primers and transformants were screened by RT-PCR for OsPsbS1 transcript levels and PsbS1 protein level. We could identify three PsbS1-RNAi lines. DOI: http://dx.doi.org/10.5564/mjas.v11i2.225 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.87-91